Penggunaan Media Pembelajaran Podcast Dalam Meningkatkan Keterampilan Menulis Puisi - Nurwiwi Putri Armin; Akmal Hamsa (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
This study aims to improve the ability to write poetry using Podcast learning media for students of class IX SMPN 27 Makassar. The sample was selected using simple random sampling technique so that the number of samples in this study was 32 students. The research instrument used was a poetry writing test. The data analysis technique used in this research is descriptive statistics. The results showed that in cycle I a total of 21 students scored below 65, while the number of students in cycle II in the low score category <65 decreased dramatically and the number of students in the higher score category <85 increased. These results show the success of Podcast media in improving students' ability to write poetry.